Ketika Agama Menyejarah - Kamaruddin Hidayat (Al-Jami'ah Research Centre, 2002)
Religions, especially Abrahamic religions, are having a great role in building human civilization in the world. History recorded that some of the greatest wonders of the world, such as pyramid in Egypt, Borobudur Temple in Indonesia, and some enormous buildings in Greece have been built under the spirit of religion. since the great role of religions nowadays religion is always attached to actual phenomena in the framework of changes in the world. This article is trying to understand religion without the border of language and culture that is local and particularistic. Abrahamic religions normatively and theologically do not share many differences. However, pragmatically and historically their differences are the big problems of the world. Most of the bloody wars that happened in some parts of the world lately are fueled by religious disagreements. Finally, pragmatically the writer explains the role of religion in the development of great civilizations in the world, including the role of religion in the democratization of Indonesia. For it, to be a democratic state, pluralism and inclusivism in understanding religion should be the heart of Indonesian society.